Bioresorbable vascular scaffold for ST elevation myocardial infarction. Issue 6 (September 2015) - Fam, Jiang Ming; Karanasos, Antonios; Regar, Evelyn; van Geuns, Robert-Jan
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.